1998
DOI: 10.2136/sssaj1998.03615995006200060020x
|View full text |Cite
|
Sign up to set email alerts
|

Classing the Soil Skeleton (Greater than Two Millimeters): Proposed Approach and Procedure

Abstract: In soil science, analytical procedures apply almost exclusively to the fine earth (<2 mm). Rock fragments or skeleton (>2 mm) are regarded as inert and discarded during sieving; however, we have found that the clasts display physical and chemical properties that can equal or surpass those of the fine earth. These properties depend largely on the degree of alteration of the clasts. In light of these findings, we developed a method to separate the rock fragments into weathering classes. This method has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 0 publications
2
40
1
Order By: Relevance
“…Soil samples collected on a volume basis were ovendried at 105°C and the bulk density (D b ) was calculated according to Corti et al (1998). The other soil samples were left to air-dry and sieved at 2 mm so as to separate fine earth and skeleton.…”
Section: Methodsmentioning
confidence: 99%
“…Soil samples collected on a volume basis were ovendried at 105°C and the bulk density (D b ) was calculated according to Corti et al (1998). The other soil samples were left to air-dry and sieved at 2 mm so as to separate fine earth and skeleton.…”
Section: Methodsmentioning
confidence: 99%
“…Thirdly, the gravel-dependent changes in soil moisture and temperature may influence soil enzyme activity (Wu et al, 2011), which is an important mediator for organic matter degradation, mineralization and nutrient recycling (Huang et al, 2013;Tripathy et al, 2014). Studies by Corti et al (1998Corti et al ( , 2002 found that rock fragments (skeleton or gravel) in stony soil with alteration contained substantial amount of organic carbon. However, SOC in the rock fragments (skeleton or gravel) was often neglected in the calculation of total soil C and N due to soil nutrition analysis mainly focused on the fine earth fraction (less than 2 mm).…”
Section: Effects Of Gravel On Soc and Tn Contentmentioning
confidence: 99%
“…A higher porosity of hard rock in the case of Pit Е-5/8 indicates more altered rock (Corti et al, 1998), probably due to differences in the porosity of the original source rock, which seems to be a prerequisite of a more pronounced step of rock disintegration and the formation of a deeper and mature profile.…”
Section: Discussionmentioning
confidence: 97%